2018
DOI: 10.5433/1679-0359.2018v39n5p2081
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and typology of dairy production systems

Abstract: The objective of this study is to analyze the typology of dairy production systems (DPS) in Paraná, Brazil, based on sustainable practices adopted by agricultural producers. A total of 153 semi-structured questionnaires containing variables for general characterization of DPS, socioeconomic characteristics of farmers, as well as environmental, social, and economic sustainability actions implemented by rural workers were applied. Common factor analysis (CFA) was used to evaluate sustainability variables. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
5
0
4
Order By: Relevance
“…The question remains the choice of the farm classifica-tion criteria and the number of distinguished groups of farms; in the mentioned studies, the latter consisted of six homogeneous groups of dairy farms. The research conducted by [87] defined three groups of farms in the typology of dairy production systems (DPSs), based on the assessment of economic, social, and environmental factors. As a result of the statistical analysis, the authors of [88] identified four groups of dairy farms differentiated by different levels of technology.…”
Section: Discussionmentioning
confidence: 99%
“…The question remains the choice of the farm classifica-tion criteria and the number of distinguished groups of farms; in the mentioned studies, the latter consisted of six homogeneous groups of dairy farms. The research conducted by [87] defined three groups of farms in the typology of dairy production systems (DPSs), based on the assessment of economic, social, and environmental factors. As a result of the statistical analysis, the authors of [88] identified four groups of dairy farms differentiated by different levels of technology.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 204 semi-structured questionnaires administered to head farmers of dairy production systems located in four mesoregions of Paraná (Central-North, Central-East, West, and Southwest) from September to November 2016 ( Figure 1). The regions were chosen because of their contribution to milk production in Paraná (IBGE, 2017) and because of the heterogeneity of dairy production systems in these regions (Brito, et al, 2015b;Gazola et al, 2018;Kuwahara et al, 2018;Zimpel, Bánkuti, Zambom, Kuwahara, & Bánkuti, 2017). Dairy production systems were chosen at random from lists provided by government technical assistance and rural extension agencies.…”
Section: Methodsmentioning
confidence: 99%
“…Si bien se han utilizado distintas variables para la tipificación de unidades de producción, las que mejores resultados aportan para el análisis de los sistemas de producción de leche son el tamaño de la unidad de producción y el nivel de producción (9) . Este método de análisis, en la actualidad, es uno de los más empleados, como queda evidenciado en recientes estudios de caso de Brasil, Colombia y México (10)(11)(12)(13) , debido a que permite encontrar más relaciones entre las variables estudiadas. Lo anterior tiene especial relevancia debido a que la producción de lácteos se lleva a cabo en todas las regiones agroecológicas del país y se tienen desde las altamente tecnificadas hasta las de subsistencia (12) .…”
Section: Introductionunclassified